Book Review: The end of poverty: economic possibilities for our time. (20th March 2006) - Rhoades, Dawna L.
The end of poverty: economic possibilities for our time, by J.D. Sachs. New York, Penguin Press, 2005. ISBN 1-59420-045-9,